EFFECTIVE METHODS OF TEACHING IN FOREIGN LANGUAGE LESSONS - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
This article discusses the effective criteria for reading and didactic analysis of the questions used in foreign language teaching on their use.